Learning Strategies for the Practice of Taboos in Shaping the Character of the Malay generation in Bintan, Kepulauan Riau, Indonesia - Yusuf HM, Muhammad; Puteh, Saifullizam Bin; Marpuah, Siti; Wahyuni, Sri (Journal of Ecohumanism, 2024)
The issue of the conduct of the nation's generation is increasingly worrisome, exacerbated by the rapid pace of globalization that further deteriorates the situation. Experts are continuously formulating ideas and strategies to improve the conduct of the nation's generation but have yet to achieve maximum results. The increasing number of ill-mannered students, disobedient children to their parents, and the high level of crime and corruption displayed by the nation's generation prove that this nation is experiencing decay. This study aims to explore and deeply understand how the practice of prohibitions can cultivate the conduct and ethics of the Malay generation. Additionally, it seeks to comprehend the challenges faced in the current practice of prohibitions and to provide an alternative to strategies for learning conduct and ethics. This study is a qualitative case study conducted through interviews using purposive sampling techniques, involving 16 study participants consisting of leaders and religious figures, academics, community leaders, and community groups. The semi-structured interview served as the primary instrument, while documentation and observation were used as secondary sources in data collection for this study. The study found that the practice of prohibitions is still upheld and serves as a proven strategy for enhancing the ethics of the Malay community in Bintan Island, Riau Archipelago, once upon a time, as it involves familial relationships as educators. However, a weakness of this strategy is its inherent dependence on outdated, superstitious, and illogical practices. The research results also indicate that the advancement of time and globalization have distanced the Malay generation from the practice of prohibitions, leading to a deterioration of conduct. Through this study, the researcher proposes a framework for an educational strategy for learning conduct as an alternative to the practice of prohibitions that is logical and easily understood by any generation.